Chronic idiopathic anhydrosis--a rare cause of heat stroke. Issue 803 (September 1992) - Dann, E. J.; Berkman, N.
Abstract : A 27 year old man presented with heat stroke following exposure to a humid, hot environment in the absence of physical exertion. Investigation revealed the presence of generalized anhydrosis without evidence of an associated disease. Although chronic idiopathic anhydrosis is rare, this entity should be considered in cases of unexplained heat intolerance and heat stroke.